Multi-omics profiling identifies M1 macrophage polarization-associated biomarkers in hepatitis B virus-related acute-on-chronic liver failure - Sun, Chengxi; Li, Cheng; Hong, Jianguo; Lv, Wencheng; Liu, Zeyang; Wang, Haochen; Dong, Qihao; Schiöth, Helgi B.; Gao, Shuai (Frontiers in Microbiology, 2025)
Background and aimsM1 macrophage polarization is essential for the progression of hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF). In this study, we aim to identify and validate M1 polarization-associated biomarkers to elucidate pathogenic mechanisms and identify potential therapeutic targets for HBV-ACLF.MethodsMulti-omics data from public databases were analyzed using a co-expression network and two differential expression analyses. Biomarkers were identified by machine learning, ROC curves, and experimental validation. A nomogram was developed to assess the diagnostic efficacy of the biomarkers. Subsequent analyses included functional enrichment, regulatory network construction, computational drug prediction, and molecular docking analysis. Finally, biomarker expression was validated using reverse transcription-quantitative PCR (RT-qPCR) in clinical specimens.ResultsCDC20, CXCL14, FCGR2B, HKDC1, and GPBAR1 were identified as diagnostic biomarkers for HBV-ACLF. The constructed nomogram showed strong diagnostic performance. Functional enrichment analysis revealed multiple pathways enriched in these biomarkers, including tryptophan metabolism and cofactor biosynthesis, etc. Subsequently, a lncRNA-miRNA-mRNA regulatory network was constructed, with key interactions such as XIST/hsa-miR-296-3p/CXCL14 and SNHG14/hsa-miR-510-5p/CXCL14. Further analysis identified multiple drugs associated with the biomarkers, including cholic acid, deoxycholic acid (GPBAR1-targeting agents). Molecular docking revealed favorable binding affinities between the predicted drugs and their targets, for example, cholic acid exhibited a binding free energy of −7.5 kcal/mol with GPBAR1. In validation experiments, RT-qPCR confirmed significant upregulation of all five biomarkers in HBV-ACLF patients compared with healthy controls (HCs).ConclusionThis study identifies CDC20, CXCL14, FCGR2B, HKDC1, and GPBAR1 as M1 polarization-associated biomarkers, revealing their roles in immune-metabolic dysregulation and proposing novel therapeutic strategies for HBV-ACLF.